ANALISIS SUMBER PENDAPATAN PETANI KELAPA SAWIT - Andriani, Evi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
This study aims to analyse and estimate farmers income derived from inside and outside the oil palm estate to the land conversion activities of palm oil. This research was conducted in Taba Gemantung village, sub-district of Merigi Sakti, Bengkulu Tengah. Sample of 37 farmers selected randomly. The analyse method used is descriptive kuantitatif. Farm income estimated by substacting total revenue with total cost. The result show that (1). Two sources f oil palm income from agriculture sectors namely, paddy field and farm labors if they do not have palm estate, (2). non agriculture income sources are builder, employees, self employed and business stalls, (3). average farm income Rp 49.641.081 per year, and (4). average off-farm income average was equal to Rp 59.954.000 years.